Just as deadly: the psychology of female serial killers - Harrison, Marissa A. (Cambridge University Press, 2023)
"In this book, Dr. Marissa A. Harrison illustrates how female serial killers differ from their male counterparts and why society is so fascinated by their grisly crimes"--